The association of CDKNB-AS1 gene polymorphism and coronary artery calcification: A systematic review - Tsuraya, Alfi; Miasih, Dewi Sekar; Ramadhani, Risa; Rohman, Mohammad Saifur; Raras, Tri Yudani Mardining (Heart Science Journal, 2026)
BACKGROUND: Coronary artery calcification (CAC) is a robust, heritable marker of subclinical atherosclerosis. Among genetic loci identified by genome-wide association studies (GWAS), 9p21 locus, particularly the CDKN2B-AS1 (ANRIL) region, has emerged as a key determinant of coronary artery disease (CAD). However, whether this signal generalizes to CAC across ancestries remains unresolved because the evidence is scattered and analytically heterogeneous, with certain populations underrepresented. OBJECTIVES: This systematic review was conducted to synthesize findings across studies that assessing CDKN2B-AS1 variants and CAC within populations. METHODS: We conducted a search in PubMed, BioMed Central, Wiley, ScienceDirect, and Cochrane from January 2010 to June 2025. Fourteen eligible studies were included in total. The JBI Critical Appraisal Checklist for Observational Studies was utilised to assess the risk of bias. Data were synthesised through a narrative approach. RESULTS: This systematic review integrates multi-ethnic evidence showing that rs1333049 and rs4977574 exhibit strong, reproducible associations with CAC severity in European and Admixed American populations, but weaker or absent effects in African and East Asian groups. In East Asia population, particularly Korean, rs10757272 shows the strongest influence. CONCLUSION: Overall, CDKN2B-AS1 functions as an important, ancestry-dependent in coronary calcification, emphasizing the need for fine-mapping and diverse cohort inclusion to achieve globally equitable genetic risk assessment.